Effect of Simulation on Psychological Empowerment of Midwifery Students Regarding the Management of Obstetric Emergencies: A Quasi-experimental Study - Nikoo Yamani; Mojgan Janighorban; Hojatollah Yousefi (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī, 2025)
Introduction: Empowering midwifery students to manage obstetric emergencies is a critical issue. Simulation can be used to train midwifery students in the management of obstetric emergencies. This study aimed to determine the effect of simulation on the psychological empowerment of midwifery students regarding the management of obstetric emergencies. Methods: This quasi-experimental study was conducted from 2017 to 2019 at Isfahan University of Medical Sciences, Isfahan, Iran. In total, 42 third-year undergraduate midwifery students ) At the end of the sixth semester of the bachelor's degree in midwifery, 26 students in the summer of 2017 for the intervention group and 22 students in the summer of 2018 for the control group (were included in the study using convenience sampling method. The intervention group participated in six simulation-based training sessions. Spreitzer's Psychological Empowerment Questionnaire was used at the start of the study, after the intervention and one year later. Repeated measures ANOVA was used to analyze the data. Results: No differences were observed between the intervention and control groups in terms of age, marital status, and grade point average .In the intervention group, a significant difference was observed before and after the intervention (P<0.001), as well as before and one year after the intervention (P<0.001) regarding the mean students' psychological empowerment scores. Immediately after the intervention, the mean psychological empowerment score in the students of the intervention group was significantly higher than that of the control group (P=0.022). One year after the intervention, there was no significant difference between the two groups (P=0.115). Conclusion:Simulation-based management of obstetric emergencies can develop midwifery students' perception of competence, self-determination, meaning, and impact more quickly and in a shorter time. It is recommended to utilize this method at regular intervals to achieve greater and more sustainable effects.